2015
DOI: 10.1089/ten.tec.2013.0622
|View full text |Cite
|
Sign up to set email alerts
|

Human Oral Mucosa Tissue-Engineered Constructs Monitored by Raman Fiber-Optic Probe

Abstract: In maxillofacial and oral surgery, there is a need for the development of tissue-engineered constructs. They are used for reconstructions due to trauma, dental implants, congenital defects, or oral cancer. A noninvasive monitoring of the fabrication of tissue-engineered constructs at the production and implantation stages done in real time is extremely important for predicting the success of tissue-engineered grafts. We demonstrated a Raman spectroscopic probe system, its design and application, for real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Khmaladze and coworkers recently proposed a non‐invasive method that allows real‐time monitoring of the thermal stress, and therefore the viability, of the EVPOME before implantation . The same group demonstrated that high levels of interleukin‐8 (IL‐8), human β‐defensin I (hBD‐I) and tissue inhibitor of metalloproteinase 2 (TIMP‐2) were predictors of healthy EVPOME .…”
Section: Keratinocyte‐based Constructsmentioning
confidence: 99%
See 3 more Smart Citations
“…Khmaladze and coworkers recently proposed a non‐invasive method that allows real‐time monitoring of the thermal stress, and therefore the viability, of the EVPOME before implantation . The same group demonstrated that high levels of interleukin‐8 (IL‐8), human β‐defensin I (hBD‐I) and tissue inhibitor of metalloproteinase 2 (TIMP‐2) were predictors of healthy EVPOME .…”
Section: Keratinocyte‐based Constructsmentioning
confidence: 99%
“…The same group demonstrated that high levels of interleukin‐8 (IL‐8), human β‐defensin I (hBD‐I) and tissue inhibitor of metalloproteinase 2 (TIMP‐2) were predictors of healthy EVPOME . Nevertheless, further clinical studies are needed, as this method appears promising not only for distinguishing stress and non‐stressed EVPOME before implantation but also for evaluating post‐grafted outcomes …”
Section: Keratinocyte‐based Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our laboratory, AlloDerm® has been used to manufacture ex vivo tissue‐engineered oral mucosa products (Khmaladze et al, ; Kuo et al, ), but Allopatch has not. In this report, we evaluated how cells cultured on AlloDerm® and Allopatch differ in terms of cellular growth and differentiation using ex vivo produced oral mucosa equivalents (EVPOMEs) as a study model (Izumi, Takacs, Terashi, & Feinberg, ; Kuo et al, ).…”
Section: Introductionmentioning
confidence: 99%